La collezione storica di farmaci dell'Università di Firenze The Historic Collection of Drugs of the University of Florence - Fiorini, Graziana; Dolara, Piero (Cataloghi e collezioni, 2004)
The is a photographic repertoire accompanied by texts in Italian and English of the collection of drugs and herbal drugs of the historical collections of the departments of Pharmacology and Plant Biology of the University of Florence. The collection includes drugs of historical interest that are still important (quinine, digitalis, aspirin, etc.), in addition to others fallen into disuse due to low activity or high toxicity and is an interesting example of the variations in medical therapy during the 20th century. The photographic images highlight the high artistic quality of glass containers and labels and underline the museum, as well as scientific, value of the collections.